Anatomia das articulações sinoviais do quadril, do joelho e tarsocrural em bugios (Alouatta belzebul Linnaeus, 1766) - França, Gustavo Lúcio Monteiro de (2020)
The howler monkey, also known as red-handed howler monkey, is a non-human primate from Atelidae family, described as an arboreal quadruped endemic to Brazil, listed as vulnerable (VU) and a specie that typically lives disjointedly distributed in some Brazilian states, in rain forests (Amazonian regions) and Atlantic forest. It was investigated the anatomical features of synovial joints of hip, knee and ankle in adults howlers monkeys (Alouatta belzebul), 5 females and 5 males, in different ages and injuries free. After the material was pinned in 10% formaldehyde, the animals were dissected, described and photographed. It was adopted the 2017 Nomina Anatomica Veterinaria for the description of anatomical terms. In order of making comparisons, and to comprehend the phylogeny, it was used the human primate (Homo Sapiens) due to larger taxonomic similarity. The hip, knee and ankle joints of the red-handed howler monkeys are similar to those described in human primate literature, considering both the shape and the extra and intra-articular anatomic structures. It’s worth mentioning some specific features of Alouatta belzebul, such as: difficulty to dissect and isolate some ligaments of hips joint, due to the adherence of those structures with the articular capsule; and the absence of some ligaments of knees and ankles joints, the feature can be explained by the necessity of larger articular mobility in the arboreal environment of the monkeys, unlike the biped displacement of human primates that requires a larger joint stability.